What factors explain the geographical range of mammalian parasites?. Issue 1903 (29th May 2019) - Byers, James E.; Schmidt, J. P.; Pappalardo, Paula; Haas, Sarah E.; Stephens, Patrick R.
Abstract : Free-living species vary substantially in the extent of their spatial distributions. However, distributions of parasitic species have not been comprehensively compared in this context. We investigated which factors most influence the geographical extent of mammal parasites. Using the Global Mammal Parasite Database we analysed 17 818 individual geospatial records on 1806 parasite species (encompassing viruses, bacteria, protozoa, arthropods and helminths) that infect 396 carnivore, ungulate and primate host species. As a measure of the geographical extent of each parasite species we quantified the number and area of world ecoregions occupied by each. To evaluate the importance of variables influencing the summed area of ecoregions occupied by a parasite species, we used Bayesian network analysis of a subset ( n = 866) of the parasites in our database that had at least two host species and complete information on parasite traits. We found that parasites that covered more geographical area had a greater number of host species, higher average phylogenetic relatedness between host species and more sampling effort. Host and parasite taxonomic groups had weak and indirect effects on parasite ecoregion area; parasite transmission mode had virtually no effect. Mechanistically, a greater number of host species probably increases both the collective abundance and habitat breadth of hosts, providing more opportunities for a parasite to have an expansive range. Furthermore, even though mammals are one of the best-studied animal classes, the ecoregion area occupied by their parasites is strongly sensitive to sampling effort, implying mammal parasites are undersampled. Overall, our results support that parasite geographical extent is largely controlled by host characteristics, many of which are subsumed within host taxonomic identity.